2005
DOI: 10.1385/abab:127:3:187
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled Metabolism Stimulated by Chemical Uncoupler and Oxic-Settling-Anaerobic Combined Process to Reduce Excess Sludge Production

Abstract: The effects of three uncoupled metabolic systems (conventional activated sludge process with the addition of 3,3', 4',5-tetrachlorosalicylanilide [TCS], oxic-settling-anaerobic [OSA] process modified by insertion of a sludge-holding tank in the sludge return line, and TCS and OSA combined process) on reducing excess sludge production were studied. Compared with the control conventional activated sludge process, the most effective system was the combined process, which could reduce excess sludge production by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This phenomenon may be attributed to the release of intracellular polymers under anoxic/anaerobic condition, which can act as floc-bridging agents to improve the settling properties of the sludge (Ye and Li, 2005), as observed for the average values obtained for SVI in OSA.R (76 mL/g and 64 mL/g, for OSA 16h .R and OSA 10h .R, respectively).…”
Section: Sludge Production and Settleabilitymentioning
confidence: 68%
See 2 more Smart Citations
“…This phenomenon may be attributed to the release of intracellular polymers under anoxic/anaerobic condition, which can act as floc-bridging agents to improve the settling properties of the sludge (Ye and Li, 2005), as observed for the average values obtained for SVI in OSA.R (76 mL/g and 64 mL/g, for OSA 16h .R and OSA 10h .R, respectively).…”
Section: Sludge Production and Settleabilitymentioning
confidence: 68%
“…Nevertheless, several studies investigating folic acid addition described no significant interference in the substrate and nutrient removal efficiencies (Dubé et al, 2002;Bertacchi, 2005). Using TCS and TCS combined with the OSA process, Ye and Li (2005) demonstrated a decline in the nutrient removal rate, with effluent concentrations that were higher compared to the control system. However, as demonstrated in this study, the authors found that the substrate removal efficiency was not affected, and the system could also stimulate an increase in the rate of specific substrate uptake (Ye and Li, 2005;Low and Chase, 1998).…”
Section: Effluent Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to a class of chemicals termed as protonophores because of their ability to shuttle electrons across the cell membrane. A number of previous studies have shown TCS to be capable of reducing the biomass yield of activated sludge cultures, effectively at lower concentrations compared to other uncouplers (Chen et al, 2000(Chen et al, , 2002(Chen et al, , 2004Ye and Li, 2005;Ye et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have successfully used this technique to monitor the impact of sludge reduction processes on sludge microbial communities. For example, the use of a chemical uncoupler led to a shift in the predominant microbial species [14,15], the oxic-settling anaerobic process (OSA) led to more abundant species [16] and thermal treatment led to the increase in thermophilic bacteria populations [17]. Recently, Tan et al [18] demonstrated that there was a change in the microbial consortia after a heat-alkaline treatment.…”
Section: Introductionmentioning
confidence: 99%